Assessing the consistency and reliability of the line intercept transect method in coral cover estimation using structure from motion photogrammetry techniques - Meng Wang; Simei Lian; Xiaofei Xiong; Jie Yang; Chenghao Chen; Xiaojun Shi (Geocarto International)
Appropriate coral reef monitoring methods and descriptors determine the effectiveness of ecosystem status assessment. We combined line intercept transect (LIT) and SfM technologies for image acquisition, and the POS information of images is defined and assigned in the relative coordinate system we build. Then, constructed high-resolution orthomosaics of coral reefs along measuring tapes in Metashape. We compared the estimates of coral cover by three methodologies (LIT, LIT on orthomosaic (LITO), surface analyses on orthomosaic (SAO)) and used virtual transects on orthomosaics and their estimates of coral cover to assess the consistency and reliability of LIT. The results show that the estimation of coral cover by LITO or LIT is more consistent and reliable when coral cover is higher, and the probability of overestimation is lower. SfM technology is increasingly used in coral reef survey and assessment, and has the potential to become the new standard for coral reef survey.